Community diagnosis in an effort to reduce the number of diarrhea cases - Syerent Lawrence; Dewi Indah Lestari (Institute of Computer Science (IOCS), 2023)
Diarrhea is the second leading cause of mortality in children under the age of five. In order to reduce the incidence of diarrhea cases in the working area of the Sindang Jaya Public Health Center. The research problem was analyzed using Blum's Paradigm. Priority problem employed non-scoring technique method (Delphi). Fishbone diagram was used to determine the root cause of the problem. Data were obtained through mini survey, pre-test, and post-test. The intervention was carried out through diarrhea counseling, demonstrations on how to make a solution of sugar and salt, and how to wash hands correctly. Monitoring was carried out using the PDCA cycle and systems approach. Therefore lifestyle was the main problem that contributes to the high cases of diarrhea. The result of the root cause was known to be a lack of public knowledge about diarrhea. The findings of the intervention increased knowledge about diarrhea, with the average post-test score of 87.33. Participants' knowledge of how to make a solution aimed to increase sugar and salt on how to wash hands properly. The problem had caused the increase in cases of diarrhea. After the community diagnosis was conducted, an increase in the knowledge of the participants who took part in the counseling was obtained. The average value of post-test counseling is above the target value. Participants could re-explain about how to make a solution of sugar and salt, and can practice how to wash hands in 6 steps correctly